Correction: Study on dynamic characteristics of salinized silt under cyclic loading. - Biao Wu; Jing Yuan Kou; Ming Min Xuan; Yu Li; Xi Yong Xu; Wen Ni Yi (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0290648.].